Sistem Informasi Pelayanan Jasa Foto Berbasis Web dengan Metode Priority Queue pada Mari Photo Studio - Fadilla, Sonya Rezky; Triase, Triase (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Mari Photo is a hobby company for people who want to do studio or outdoor photography for whatever needs, such as graduation photography or model photography. Mari Fotostudio Setia Budi still has several obstacles in the service system for consumers related to the lack of service because many customers come, causing less than optimal service to customers. The purpose of this research is to design a service information system that can overcome existing problems to build a service information system using the priority queue method at Mari Photo Studio and improve the performance of photo services for customers. And also use the system development method with the prototype method in making the application design. The system built with the priority queue method that has been developed can make it easy for customers to order services at Mari Photo Studio Setia Budi.